2016
DOI: 10.1038/srep18493
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-induced miRNA expression changes in cultured rat astrocytes

Abstract: Hepatic encephalopathy is a neuropsychiatric syndrome evolving from cerebral osmotic disturbances and oxidative/nitrosative stress. Ammonia, the main toxin of hepatic encephalopathy, triggers astrocyte senescence in an oxidative stress-dependent way. As miRNAs are critically involved in cell cycle regulation and their expression may be regulated by oxidative stress, we analysed, whether astrocyte senescence is a consequence of ammonia-induced miRNA expression changes. Using a combined miRNA and gene microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
(74 reference statements)
2
26
0
Order By: Relevance
“…Studies elaborated that the NRF2 pathway was involved in brain edema caused by various factors (Yang et al, 2016;Gao et al, 2018;Jin et al, 2018). Although some studies analyzed that AHEinduced astrocyte edema was related to the downstream gene HO-1 of the NRF2 pathway (Oenarto et al, 2016), there is no evidence that it is directly related to NRF2 pathway. Therefore, we assumed that the occurrence of brain edema caused by AHE may be related to the NRF2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies elaborated that the NRF2 pathway was involved in brain edema caused by various factors (Yang et al, 2016;Gao et al, 2018;Jin et al, 2018). Although some studies analyzed that AHEinduced astrocyte edema was related to the downstream gene HO-1 of the NRF2 pathway (Oenarto et al, 2016), there is no evidence that it is directly related to NRF2 pathway. Therefore, we assumed that the occurrence of brain edema caused by AHE may be related to the NRF2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could well be that different models and/or different time points of analysis can at least partly explain these results. We noticed that the large majority of studies investigating acute as well as chronic in vitro and in vivo HE models address toxic effects of hyperammonemia after one day, few days, or even after weeks (Görg et al, 2015; Hazell and Norenberg, 1998; Oenarto et al, 2016; Qvartskhava et al, 2015). Very little is known about the immediate effect of ammonia on brain energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, along with disturbances of the mitochondrial morphology an imbalance of various energy metabolism pathways have been suggested as consequences of hyperammonemia, however, the effects and their possible contribution to the pathogenesis of HE are still unclear. In most studies prolonged treatments, such as 24 hours and beyond, have been used and are quite well studied (Görg et al, 2015; Hazell and Norenberg, 1998; Oenarto et al, 2016). However, the early events upon exposure to high ammonia concentrations are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…They were interested in the ammonia-dependent senescence observed in astrocytes and its relationship with miRNAs. By means of miRNA array experiments, they found that 43 of 336 miRNAs were significantly downregulated in hyperammonemic conditions, six of which (miR-31a-5p, miR-221-3p miR-221-5p, miR-222-3p, miR-326-3p, and miR-365-3p) seem to bind and regulate the mRNA encoding the heme oxygenase 1 (HO-1) protein; four of these miRNAs (miR-31a-5p, miR-221-3p, miR-222-3p, and miR-326-3p) were prevented to be downregulated by NH4Cl treatment, when astrocytes were exposed to the glutamine synthase inhibitor, methionine sulfoximine (MSO); moreover, the NADPH oxidase inhibitor, apocynin, fully prevented NH4Cl-mediated downregulation of the four miRNAs predicted to target HO-1, indicating that senescence is regulated by miRNA expression in cultured astrocytes and partly regulated by glutamine synthesis and NADPH-oxidase activity [63]. Data recently obtained in our laboratory indicate that three miRNAs (miR-29a-5p, miR-29b-3p, and miR-148b-3p) are repressed in brain tissue of a mouse model of liver cirrhosis.…”
Section: Genetic and Epigenetic Effects Induced By He In Astrocytesmentioning
confidence: 99%